Strategic Decision Making in Fire Risk Management in Aftab Gorgan Commercial Complex using Artificial Intelligence Model - Bijan MAGHSOUDI KAMAL; Reza JAFARI NODOUSHAN; Mohammad NOURI (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract: Introduction: Today, commercial complexes are among the most important shopping centers in cities that account for one of the most important urban development infrastructures. Evaluation and management of fire is essential to prevent accidents and disasters such as fires. Due to the increased population density and slow access to safe and secure outdoor space during the disaster, human casualties and financial losses have increased. The aim of this study was to make strategic decisions in fire risk management in Aftab Gorgan commercial complex using artificial intelligence model. Method: In this study,  all technical documentation, including technical-physical and urban properties as well as notification and extinguishing system of the commercial complex under study were investigated. Later, the important and influential components of the design were identified, paired, weighted, and compared using Delphi questionnaires. In the next stage,  the SWOT matrix was applied and quadratic strategies were designed and modeled after designing a hierarchical tree to model and prioritize the strategies. Results: According to the outputs of the performed modeling using Matlab and Neuro-Solution 5 software, we found that in weighting and ranking of the eight designed strategies, only one strategy was ranked (and has equal priority) in both models and other scenarios were different. Therefore, integrating strategies for fire risk management was considered essential. Conclusion: The findings showed that the strategy of adopting the systematic and strategic-operational management approach of fire risk in Gorgan Aftab 3 Complex design were the most ideal possible strategies. This was due to the special attention paid to optimization of physical spaces and fire alarm systems as well as implementation of business classification and continuous excellence system of HSE-MS and crisis management.